2012
DOI: 10.1111/j.1476-4431.2012.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rest temperature, contact activation, and sample technique on canine thrombelastography

Abstract: Objective To determine the effects of rest temperature, contact activation (CA), and sample collection technique on thrombelastography (TEG) using canine whole blood. Design Prospective, experimental study. Setting University‐based research facility. Animals Twelve healthy, adult, mixed‐breed dogs. Interventions Blood was collected by jugular venipuncture. Tubes containing 3.2% sodium citrate, with and without 75 μg/mL corn trypsin inhibitor (CTI), were filled by vacuum. Samples rested for 30 minutes at 3 temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Because this study was conducted retrospectively, the timing of sample collection for TEG relative to death and necropsy was not standardized, which also may have affected results. 63 However, there was no association between necropsy evidence of thrombosis and duration of time between TEG and necropsy. In addition, only previously collected and processed tissue was available for retrospective histopathologic review, and evidence of thrombosis or infarction may have been missed in tissues that were not saved.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Because this study was conducted retrospectively, the timing of sample collection for TEG relative to death and necropsy was not standardized, which also may have affected results. 63 However, there was no association between necropsy evidence of thrombosis and duration of time between TEG and necropsy. In addition, only previously collected and processed tissue was available for retrospective histopathologic review, and evidence of thrombosis or infarction may have been missed in tissues that were not saved.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the relatively small number of cases in this study may have introduced Type II error. Because this study was conducted retrospectively, the timing of sample collection for TEG relative to death and necropsy was not standardized, which also may have affected results . However, there was no association between necropsy evidence of thrombosis and duration of time between TEG and necropsy.…”
Section: Discussionmentioning
confidence: 95%
“…The second (LOE 3, Good) investigated TEG results in clinically healthy dogs using jugular vein blood samples obtained using a butterfly catheter and vacuum tube (discard tube used) with those obtained using direct venipuncture and syringe aspiration (no discard tube). Syringe‐drawn samples had significantly shorter R time; however, no other significant differences were observed …”
Section: Evidence Summarymentioning
confidence: 99%
“…11,12 In a recent study 13 in humans, investigators suggested that only those patients who had changes in thromboelastography tracings after treatment with LMWH benefited from that treatment, regardless of the AXA. Thromboelastography may be activated by stimulating the intrinsic pathway (through recalcification 16 or exposure of the sample to kaolin) or the extrinsic pathway (through the addition of tissue factor to the reaction). 14 The effect of LMWH (dalteparin) on a modified thromboelastography assay has been investigated in an in vitro study in dogs.…”
mentioning
confidence: 99%